DIVING DEEP: UNDERSTANDING INNOVATIVE WORK BEHAVIOR THROUGH THE LENS OF CONSERVATION OF RESOURCES THEORY - Indrayani, I Gusti Ayu Putu Wita (JURNAL KEPARIWISATAAN, 2025)
This study focuses on the innovative behavior of millennials workers to calibrate the premises in Conservation of Resources Theory as a macro theory in this research area. An explanatory sequential design was applied through the Smart PLS analysis. Data were collected through a cross-sectional survey of 129 millennial workers at starred hotels and validated through in-depth interviews. The findings of the study indicate that happiness at work fully mediates the effect of psychological capital on innovative work behavior. This confirms premises in conservation theory which postulates that psychological capital offers psychological resources that enable employees to experience job happiness, which in turn fosters the development of innovative behavior. Several dimensions play an important role in the formation of innovation through work happiness, namely a positive work environment, career development opportunities and flexibility, work-family balance, recognition and appreciation. The practical implications of this study offer recommendations for star hotel management to enhance organizational culture that fosters employees’ happiness at workplace by implementing recognition and appreciation programs, providing work-life balance facilities, and strengthening positive work relationships. Theoretically, these findings align with the conservation of resources theory which is emphasizing the reinforcement of internal resources to support innovative work behavior.